Konsep Evaluasi Pembelajaran Pendidikan Agama Islam di Perguruan Tinggi Umum dalam Perspektif Syed Muhammad Naquib al-Attas: Concept of Learning Evaluastion of Islamic Religious Education Courses in Public Universities From The Perspective of Syed Muhammad Naquib al- Attas - Mahardika Putera Emas; Ismail; Nurhilaliati (Educan, 2024)
The background of this research is the issue of PAI courses at public universities, which is still inadequate. It felt that the determination of PAI courses as national compulsory courses is still insufficient to achieve its objective or national educational goals. Insufficient study hours, material that still tends to be descriptive, and the inability to answer students’ personal needs ultimately become a scourge when conducting learning evaluations. The milieu of a public university, which differs drastically from lower levels, requires an appropriate evaluation model. Syed Muhammad Naquib al-Attas, a world-class thinker from Malaysia, has some unique educational ideas that can inspire, including evaluation. Moreover, he has directly led a higher education institution, which has become a reference for many universities today. This research elaborates on the concept of al-Attas learning evaluation in the context of PAI courses at public universities. This research shows that the evaluation philosophy and practice carried out by al-Attas could become a milestone for reforming the principles and practices of PAI courses at public university, especially in learning evaluation. In order to achieve its objectives, this research uses a library research method by examining the relevant primary and secondary sources.